1998
DOI: 10.1080/00288233.1998.9513293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potato mirid(Calocoris norvegicus)on white clover seed production in small cages

Abstract: Potato mirid, Calocoris norvegicus, commonly occurs in white clover, Trifolium repens, crops in Canterbury, New Zealand. Its potential to reduce seed yield by feeding injury was investigated in field cage plots in a cv. Huia white clover seed crop. Third to fifth instar nymphs were released at five intensities ranging from 0 to 2 mirids per 5 stolons. Plant growth and inflorescence production were determined by regular measurements of 15-20 tagged stolons per cage. Seed was harvested in late summer and dressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Generally, C. norwegicus inflicts feeding damage by piercing plant tissues, secreting digestive enzymes and pumping out the fluid plant material. In alfalfa, white clover and lotus, feeding results in the shrivelling of seeds and proliferation of secondary stems (Macfarlane et al, 1981;Wightman & Macfarlane, 1982;Wightman & Whitford, 1982;Clifford et al, 1983;Chapman, 1984;Schroeder et al, 1998;Wheeler, 2000). Schroeder et al (1998) demonstrated that feeding injury inflicted by C. norwegicus has the potential to significantly reduce white clover seed yield causing estimated losses of up to $740 ha x1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, C. norwegicus inflicts feeding damage by piercing plant tissues, secreting digestive enzymes and pumping out the fluid plant material. In alfalfa, white clover and lotus, feeding results in the shrivelling of seeds and proliferation of secondary stems (Macfarlane et al, 1981;Wightman & Macfarlane, 1982;Wightman & Whitford, 1982;Clifford et al, 1983;Chapman, 1984;Schroeder et al, 1998;Wheeler, 2000). Schroeder et al (1998) demonstrated that feeding injury inflicted by C. norwegicus has the potential to significantly reduce white clover seed yield causing estimated losses of up to $740 ha x1 .…”
Section: Introductionmentioning
confidence: 99%
“…Potato bugs overwinter as eggs oviposited in woody plants or herbs (Kullenberg, 1944;Southwood & Leston, 1959;Purcell & Welter, 1990a) and thus, hedgerows and field margins are preferred overwintering habitats from which nymphs invade field crops in early spring (Afscharpour, 1960;Schroeder & Clifford, 1996). Therefore, suggested techniques for managing C. norwegicus include the removal and control of host plants in hedgerows adjacent to fields as well as the application of pesticides along the field edges (Hartley et al, 1982;Purcell & Welter, 1991;Schroeder et al, 1998;Rice & Bentley, 2005). However, ecological infrastructures, such as hedgerows and grass or wild flower strips, are essential for the development and efficiency of natural enemies of crop pests, providing refuges, hibernation areas, prey for juvenile stages of predators and essential food sources (e.g.…”
Section: Introductionmentioning
confidence: 99%